Comparison of Vitek MS and MALDI Biotyper for Identification of Actinomycetaceae of Clinical Importance - Ferrand, Janina (J Clin Microbiol, 2016)
The Vitek MS in vitro diagnostic (IVD) and MALDI Biotyper IVD systems were evaluated for the identification of 158 strains of Actinomycetaceae. Correct species-level identification rates of 60.7% and 58.2% were obtained with the Vitek MS system after direct deposit and with the MALDI Biotyper system after on-plate formic acid treatment, respectively.